Investigations on metal injection molding of 316L SS using Thermoplastic Natural Rubber (TPNR) binder as a new system - Hassan, Norita; Hassan, Noor Azlina; Haji Ahmad, Sahrim (Trans Tech Publications Ltd., Switzerland, 2012)
Metal injection molding (MIM) is a near net-shape manufacturing technology that is capable of mass production of complex parts cost-effectively. The unique features of the process make it an attractive route for the fabrication of the new binder system since the success of MIM process is dependent on the outward appearance of the resultant feedstock. Thermoplastic natural rubbers (TPNR) blends consist of thermoplastics, such as polyethylene (PE), alloyed with natural rubber (NR) with different thermoplastic to NR ratios. The soft grade TPNR is produced by blends with compositions richer in rubber while the harder grades can contain up to about 30 % NR. This study investigates the influence of new binder system consisting of TPNR on injection parameter, density of injected molded specimen and changes during solvent extraction. Results show that TPNR plays an important role as a good binder system and shortens the solvent extraction process.